ISSUES OF HARMONIZING NATIONAL STANDARDS WITH INTERNATIONAL STANDARDS IN PREPARING FINANCIAL STATEMENTS - G‘аniyеv Zаfаr Usаnоvich (American Journals, 2025)
This scientific article discusses the need to prepare and adapt the balance sheet, compiled based on national standards, to international accounting standards and to provide it to external users within the established timeframe.
Keywords: Transformation, parallel accounting, international accounting standards, financial reporting, balance sheet, assets, liabilities, equity.